1989
DOI: 10.1093/jaoac/72.6.912
|View full text |Cite
|
Sign up to set email alerts
|

Precolumn Phenylisothiocyanate Derivatization and Liquid Chromatography of Amino Acids in Food

Abstract: A precolumn phenylisothiocyanate derivatization method is described for the determination of amino acids in protein hydrolysates from a wide variety of complex food matrixes, with and without performic acid oxidation pretreatment. Analysis of samples that were not pretreated with performic acid was necessary since this pretreatment destroyed an average of 25% of the histidine and 87% of the tyrosine present in the food samples. This method is rapid and reproducible; coefficients of variation between duplicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
1
8

Year Published

1996
1996
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 0 publications
0
95
1
8
Order By: Relevance
“…The amino acid composition of both protein hydrolysates was performed according to the method MA-009 (Hagen, Frost, & Augustin, 1989;White, Hart, & Fry, 1986) in a commercial laboratory (CBO Análises Laboratoriais Ltda. ; Table 3).…”
Section: Chemical Analysismentioning
confidence: 99%
“…The amino acid composition of both protein hydrolysates was performed according to the method MA-009 (Hagen, Frost, & Augustin, 1989;White, Hart, & Fry, 1986) in a commercial laboratory (CBO Análises Laboratoriais Ltda. ; Table 3).…”
Section: Chemical Analysismentioning
confidence: 99%
“…Method (oxidation+hydrolysis+derivatization). The method we used to check the accuracy of hydrolysis and oxidation was similar to that of Hagen et al (1989). The content of amino acids in a protein, ␤-casein (representative of the matrix studied) was measured in triplicate.…”
Section: Analytical Parametersmentioning
confidence: 99%
“…Although HPLC has been used in the study of amino acids, a review of published studies revealed that most of them have focused on the application of hydrolysis and previous treatment to protect CYS and MET in foods such as fish meal, maize corn meal, mixed feed, soybean meal, meat meal, whey powder, egg white and beef, etc.) (Sarwar et al, 1983;Elkin, 1984;Spindler et al, 1984;Gehrke et al, 1985;MacDonald et al, 1985;Elkin and Wasynczuk, 1987;Iwaki et al, 1987;Hagen et al, 1989;Cubedo Fernández-Trapiella, 1990;Van Der Meer, 1990) or pure proteins such as casein, ␤-lactoglobulin, lysozyme, etc.) (Sarwar et al, 1983;Bidlingmeyer et al, 1984;Cohen et al, 1984Cohen et al, , 1986Gehrke et al, 1985;MacDonald et al, 1985;Hagen et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations